The clinical diagnosis of stroke and stroke subtypes - Caplan, Louis (Henry Stewart Talks, 2008)
Sequential hypothesis-driven data acquisition, History-taking, Physical examinations, Neurological examinations, Brain imaging, Vascular imaging
Archived at 2022/01/31